Combinations of an acetyl CoA carboxylase inhibitor with hepatic lipid modulating agents do not augment antifibrotic efficacy in preclinical models of NASH and fibrosis. Issue 9 (23rd June 2022) - Vijayakumar, Archana; Okesli‐Armlovich, Ayse; Wang, Ting; Olson, Isabel; Seung, Minji; Kusam, Saritha; Hollenback, David; Mahadevan, Sangeetha; Marchand, Bruno; Toteva, Maria; Breckenridge, David G.; Trevaskis, James L.; et al.
Abstract: Dysregulated hepatocyte lipid metabolism is a hallmark of hepatic lipotoxicity and contributes to the pathogenesis of nonalcoholic steatohepatitis (NASH). Acetyl CoA carboxylase (ACC) inhibitors decrease hepatocyte lipotoxicity by inhibiting de novo lipogenesis and concomitantly increasing fatty acid oxidation (FAO), and firsocostat, a liver‐targeted inhibitor of ACC1/2, is under evaluation clinically in patients with NASH. ACC inhibition is associated with improvements in indices of NASH and reduced liver triglyceride (TG) content, but also increased circulating TG in subjects with NASH and preclinical rodent models. Here we evaluated whether enhancing hepatocyte FAO by combining ACC inhibitors with peroxisomal proliferator‐activated receptor (PPAR) or thyroid hormone receptor beta (THRβ) agonists could drive greater liver TG reduction and NASH/antifibrotic efficacy, while ameliorating ACC inhibitor–induced hypertriglyceridemia. In high‐fat diet–fed dyslipidemic rats, the addition of PPAR agonists fenofibrate (Feno), elafibranor (Ela), lanifibranor (Lani), seladelpar (Sela) or saroglitazar (Saro), or the THRb agonist resmetirom (Res), to an analogue of firsocostat (ACCi) prevented ACCi‐induced hypertriglyceridemia. However, only PPARα agonists (Feno and Ela) and Res provided additional liver TG reduction. In the choline‐deficient high‐fat diet rat model of advanced liver fibrosis, neither PPARα (Feno) nor THRβ (Res) agonism augmented the antifibrotic efficacy of ACCi. Conclusion : These data suggest that combination therapies targeting hepatocyte lipid metabolism may have beneficial effects on liver TG reduction; however, they may not be sufficient to drive fibrosis regression. Abstract : Here we evaluated whether combinations of an acetyl CoA carboxylase inhibitor with agents that modulate hepatocyte lipotoxicity would synergistically decrease liver triglyceride and inhibit fibrosis progression in rodent models. Our data clearly demonstrate that some combinations have synergistically lower liver TG without inhibiting fibrosis progression. image